Effect of peppermint oil on hair growth and hair fall reduction in individuals with diffused hair loss: A randomized controlled study - S, Malarvizhi; Deepa, Y.; M, Muthulakshmi.; P, Saranya.; Christa, Edmin; Mooventhan, A. (Indian Journal of Integrative Medicine, 2025)
Introduction: Diffuse hair loss is the condition where hair shedding is seen across the scalp in uniform distribution, which is the result of a disruption of one phase of the hair cycle. Up to 85% of males and 40% of females are affected by hair loss and its incidence increases with age for both sexes. Hair shedding in females is common and relating to the nutritional and endocrinal factors. Aim: The aim of the study is to evaluate the effect of peppermint essential oil mixed with coconut oil on hair fall reduction in individuals with unhealthy hair fall rate of over 200 strands of hair/day. The effect on hair density, itching of the scalp, hair growth, amount of noticeable new hair, visibility of the scalp and rate of hair loss in individuals is evaluated. Materials and methods: Sixty females aged 20.52±2.14 years were randomly allocated to either the study group or control group. The study group received head massage using peppermint oil mixed with coconut oil, whereas the control group received head massage using coconut oil for 2-3 minutes a day, 3 days a week for 1 month. Assessments were taken at before and after the intervention. Four Item Women’s Hair Growth Questionnaire (FIWHGQ) was considered, and the Kolmogorov Smirnov test was used to check normality. Baseline and demographic details of study group and control group were compared by independent samples-t-test or Mann Whitney-U-test, and within-group analysis was done using paired samples t-test or Wilcoxon Signed Rank test based on the data distribution. Results: Hair count and itching: Within group analysis showed a significant increase in mid-pattern hair count (p = 0.034) with an insignificant (slightly missed the level of significance) increase in frontal hair count (p = 0.096) and vertex hair count (p = 0.056) with the significant reduction in itching (p = 0.005) in the study group, whereas the control group showed a significant increase in frontal hair count (p=0.001) and no significant changes mid-pattern and vertex hair count and itching. However, between group analysis showed no significant difference between the study and control groups. Conclusion: Peppermint oil can be used as an alternative remedy for hair fall and itching of the scalp.